An optimal cropping plan for increasing crop productivity and farm income in a selected coastal area of Bangladesh - Sarker, FIM Golam Wahed; Jaim, WMH (Bangladesh Rice Journal, 2015)
This study was undertaken in a selected coastal area of Bangladesh to determine the optimal allocation of farm resources among different crops for increasing crop productivity and farm income. Farm survey method was used to collect data in order to develop linear programming representative farm models. The analysis takes into account crop activities, inputs used, farm size and land types. Optimal plans show mis allocation of existing resources and indicate considerable scope for increasing farm productivity and income by reallocation of existing resources. The mis allocation of resources on large farms was greater than that of small farms. The analysis suggests that by reallocating existing resources, large farms could increase farm income and employment more significantly than the small farms. The research supports the view that the government should maintain a policy that favours optimal allocation of farm resources in coastal area and the extension and NGO workers may provide guidelines to farmers for better allocation of existing farm resources and thus increases crop productivity and farm income in coastal area of Bangladesh. Bangladesh Rice j. 2014, 18(1&2): 65-72